The impact of the financing structure on investment decisions : Applied research in a sample of commercial banks listed in the Iraq Stock Exchange for the period (2011-2020) (Journal of Accounting and Financial Studies ( JAFS ), 2023)
The research aims to shed light on the financing structure, which is one of the important pillars of financial management in the commercial banking sector, which enhances its financial position through financing its various investments, which is one of the pillars of the successful economy of the commercial banking sector. in which country. The contents of the research variables, which were represented by the independent variable, financing structure, the dependent variable, and investment decisions in commercial banks, which the researcher tried to address, as the research began with a basic variable that depends on diagnosing the impact of the financing structure on and its reflection on investment decisions in commercial banks. Research sample The researcher started from the research hypothesis of the impact of the financing structure on investment decisions, by selecting a set of indicators and subjecting them to the method of comparative financial analysis, which is represented by indicators measuring the independent variable, which is the financing structure to reveal its components. (equity ratio, deposit ratio, loan ratio, debt ratio) As for indicators measuring the variable related to the axis of investment decisions to reveal the extent to which the basic objectives of banks are achieved, which are (liquidity ratio, legal reserve ratio), which refer to the most important pillars on which investment decisions are based. in commercial banks. As for the study sample, a sample of the research consisting of two banks (the National Bank of Iraq and the Credit Bank) was selected for research and a ten-year time series (2011-2020) for investment through the optimal diversification of the resources available in the commercial bank in different forms. As for the recommendations, they depend on experts and those with experience in the field of financing in determining the appropriate financing for the bank